1999
DOI: 10.1016/s0893-133x(99)00041-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antidepressants on 5-HT7 Receptor Regulation in the Rat Hypothalamus

Abstract: Recent evidence suggests that a novel serotonin receptor 5-HT 7 localized in the hypothalamus downregulates in response to treatment with the antidepressant fluoxetine (Sleight et al. 1995). This receptor has also been implicated in the regulation of circadian rhythms (Lovenberg et al. 1993). Here Depression may involve many possible abnormalities corresponding to multiple biological correlates of dysfunction or dysregulation in either one or several brain neurotransmitter systems (Cooper et al. 1996;Nair and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(104 citation statements)
references
References 84 publications
0
101
0
1
Order By: Relevance
“…As shown in a previous study, aging is associated with a decrease in serotonin transporter binding in the hamster DRN (Duncan and Hensler, 2002), which would be likely to contribute to reduced serotonin reuptake and therefore increased extracellular serotonin concentrations that could induce 5-HT 7 receptor down regulation. This possibility is supported by findings that chronic treatment with serotonin selective reuptake inhibitors decreases 5-HT 7 receptor binding sites in rats (Mullins et al, 1999;Sleight et al, 1995).…”
Section: Discussionmentioning
confidence: 86%
“…As shown in a previous study, aging is associated with a decrease in serotonin transporter binding in the hamster DRN (Duncan and Hensler, 2002), which would be likely to contribute to reduced serotonin reuptake and therefore increased extracellular serotonin concentrations that could induce 5-HT 7 receptor down regulation. This possibility is supported by findings that chronic treatment with serotonin selective reuptake inhibitors decreases 5-HT 7 receptor binding sites in rats (Mullins et al, 1999;Sleight et al, 1995).…”
Section: Discussionmentioning
confidence: 86%
“…The relatively high density of 5-HT 7 in the limbic and thalamocortical regions hints at a possible role of the receptor in mediating depressive disorders. Downregulation of 5-HT 7 has been observed after chronic antidepressant treatment, 30 and several antipsychotics and antidepressants (such as clozapine, zotepine, risperidone, pimozide, and fluoxetine) have been found to bind with high affinity at 5-HT 7 receptors. 31 It is still not conclusively known, however, whether and to what extent these actions contribute to therapeutic effects.…”
Section: -Ht 7 : Therapeutic Possibilitiesmentioning
confidence: 99%
“…Furthermore, inactivation or pharmacological blockade of the 5-HT 7 receptor lead to changes in rapid eye movement sleep that are opposite to those seen in depression [8,13]. In addition, it has been shown that certain antidepressants might exert some of their effects by acting directly at the 5-HT 7 receptor [26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, inactivation or pharmacological blockade of the 5-HT 7 receptor lead to changes in rapid eye movement sleep that are opposite to those seen in depression [8,13]. In addition, it has been shown that certain antidepressants might exert some of their effects by acting directly at the 5-HT 7 receptor [26].Obsessive-compulsive disorder (OCD) is a debilitating disease with an overall prevalence of close to 1 % [15]. There is strong evidence in support of a significant role for 5-HT in OCD and antidepressant drugs, mainly selective serotonin reuptake inhibitors (SSRIs), are the pharmacological treatment of choice for OCD [4,15].…”
mentioning
confidence: 99%